ANALISIS KUALITAS PELAYANAN PADA PT. REKREASINDO NUSANTARA DI MAKASSAR - Helmy Syamsuri (Jurnal Bisnis dan Kewirausahaan, 2015)
The purpose of this study was to analyze the quality of service at PT Nusantara Rekreasindo in Makassar which is based on the level of importance (importance) of visitors to the performance (performance) services provided by PT Nusantara in Makassar.Penilaian Rekreasindo will be the quality of service developed by Leonaed L.Barry, A. Parasuraman and Zeithmal (Kotler, (2008: 53), known as service quality (SERVQUAL), which is based on five dimensions of quality that is tangilbles (direct evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee) and empathy ( empathy). Analyzing the quality of service by using analisisa namely Importance and Performance Matrix, which consists of four quadrants where each variable was analyzed in one quadrant will give a different meaning as well as the treatment is also different. The level of quality of service PT Rekreasindo archipelago Makassar that there is a difference (gap) between the level of visitor interest with the services provided by PT. Nusantara Rekreasindo in Makassar.